Understanding dynamic friction of rock fractures - Koo, Cheng Yang (2019)
This report examines the dynamics of a fault fracture slip due to changes in loading on the fault. The report investigates the spectrum of fault slip modes, from the observed stick-slip mechanics, as well as through understanding of the well-established rate-and-state-dependent friction laws. The report will be based on a series of mechanical stick-slip fault sliding experiments. The experiments will be conducted on a polycarbonate fault interface, to measure changes in shear stress, shear displacement, absolute energy, and to also study the different spectrum of fault slip modes with evolution in dynamic friction.